Living and breathing the brand: The role of internal communication - Harkness, James (Journal of Communication Management, 1999)
Branding is becoming increasingly recognised as crucial to business success. A brand is a promise of the goods and service a customer will receive from an organisation. If the organisation is to succeed, everyone working for the company must live and breathe the brand values. This paper focuses on how effective internal communication can ensure that people feel part of the brand and deliver on its promises. It discusses best practice methodology and draws on practical examples from Woolwich plc and Smithkline Beecham.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTEwOC9lYjAyMzUxMA